How Organizational Commitment Explains The Effect Of Leadership And Work Quality On Organizational Citizenship Behavior - Lovienna Reisha; Fredianaika Istanti (UNIVERSITAS PAKUAN, 2026)
Organizational Citizenship Behavior (OCB) is an important factor that supports the effectiveness and well-being of a company, especially in the hospitality industry which relies heavily on employees' extra contributions. This study aims to analyze the factors that influence Organizational Citizenship Behavior among employees of Kiyana Hotel in one chain, focusing on the influence of Transformational Leadership and Quality of Work Life as well as the mediating role of Organizational Commitment. This study uses a quantitative approach with a probability sampling method through a census sampling technique. The data collection instrument used a questionnaire with a Likert scale. The study population was all employees totaling 43 respondents. The study sample consisted of 35 employees of Kiyana Premiere Hotel Batang and 8 employees of Kiyana Resort Dieng as respondents. Data analysis was conducted using SEM-PLS to test the relationship between variables simultaneously. The results of the study show: Transformational Leadership and Quality of Work Life have a positive and significant effect on Organizational Citizenship Behavior; Transformational Leadership and Quality of Work Life have a positive and significant effect on Organizational Commitment; Organizational Commitment has a positive and significant effect on Organizational Citizenship Behavior; Organizational Commitment mediates Transformational Leadership and Quality of Work Life on Organizational Citizenship Behavior; These findings underscore the importance of inspiring leaders and a work environment that supports employees' quality of life in building high levels of commitment, ultimately encouraging extracurricular behaviors that benefit the company. This research offers practical implications for hotel management in designing leadership strategies and improving work quality to enhance overall employee contribution.